The Impact of Tin Mining Activities and Its Integration in Science Learning - Dewi, Tisrin Maulina; Rahayuningsih, Margareta; Marianti, Aditya (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
Karimun Regency in Riau Islands Province is one of the regencies as a tin producer in Indonesia. This study aims to describe the impact of tin mining activities in Karimun Regency and its integration into science learning. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and literature studies. The research results indicate that tin mining activities on land would create former tin mine pits that have positive and negative impacts. The positive impact is that these former tin mine pits could be a source of income for the community like being a source of water during the dry season and a tourist attraction. While the negative impact is that it could damage the environment and require a relatively long time to recover. Efforts need to be made to utilize these former tin mine pits properly so that they can function properly and they can benefit the community. Therefore, science learning based on the environment of tin mining activities needs to be integrated into the learning process in schools so that later it can increase students' knowledge about the importance of an attitude of protecting the environment and having sustainable environmental awareness.